Assessment on the Postproduction Systems and Losses of Calamansi in the Philippines: Oriental Mindoro to Manila Market Chain - Calica, Gigi B.; Nacion, Niña Kathleen F. (International Journal of Scientific Research and Management (IJSRM), 2024)
Calamansi (Citrofortunella microcarpa) also known as calamondin, or Philippine Lime is considered one of the high value crops indigenously and commercially grown in the Philippines. A steady decline in the volume of production was recorded from 2016 to 2022 wherein postproduction losses was as one of the factors identified. Using the chain of Oriental Mindoro to Manila market, this study was conducted to assess the present situation compared to the 2009 postproduction systems and perceived loss figure. Results showed that there was a shift in the harvesting time, more careful harvesting using the metal clip to minimize plugging, incorporating washing and curing and more market outlets identified in the present postproduction system. It was evident that total perceived losses by the different stakeholders were reduced at 17.07% from 30% of 2009. Farm losses contributed the highest and sources of losses were due to insect damage, yellowing, and browning. Majority of the calamansi produced in Oriental Mindoro were supplied to Divisoria, Manila and Tanuan, Batangas markets. Among the chain actors, farmers incurred the highest costs while wholesaler received the highest net income. Farm activities were predominantly done by males while females for the marketing and processing. Processing the marketable rejects and the volume during peak seasons’ glut is recommended through farmer’s cooperative/associations as value adding activities.